2015
DOI: 10.1186/s12885-015-1514-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced efficacy of photodynamic therapy by inhibiting ABCG2 in colon cancers

Abstract: BackgroundPhotodynamic therapy (PDT) contains a photosensitizing process, which includes cellular uptake of photosensitizer and delivery of light to the target. ATP-binding cassette subfamily G2 (ABCG2) regulates endogenous protoporphyrin levels. In human colon cancers, it is not fully examined the role of ABCG2 in porphyrin-based photodynamic therapy.MethodsSW480 and HT29 cells were selected because they showed low and high ABCG2 expression levels, respectively. Pyropheophorbid-a (PPa) was used as a photosens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…Focusing on heme, it has been shown that triple negative breast cancer cell lines have significantly reduced ALA-PpIX levels as compared with estrogen receptor (ER) positive and human epidermal growth factor receptor 2 (HER2) positive breast cancer cell lines because of elevated ABCG2 activity (95). In line with this, high ABCG2 expression was considered a major cause of failure of ALAphotodynamic therapy in different kinds of tumors, as it can induce resistance to this kind of treatment by preventing the accumulation of the photosensitizer PpIX inside the cells (96,97). Moreover, in an in vitro model of myeloid leukemia, it has been shown that MYCN drives increased heme synthesis and that, in this system, the excess of PpIX produced is promptly exported out of the cells by ABCG2 to avoid cell toxicity (45).…”
Section: Heme Import/export/degradation and Cancermentioning
confidence: 99%
“…Focusing on heme, it has been shown that triple negative breast cancer cell lines have significantly reduced ALA-PpIX levels as compared with estrogen receptor (ER) positive and human epidermal growth factor receptor 2 (HER2) positive breast cancer cell lines because of elevated ABCG2 activity (95). In line with this, high ABCG2 expression was considered a major cause of failure of ALAphotodynamic therapy in different kinds of tumors, as it can induce resistance to this kind of treatment by preventing the accumulation of the photosensitizer PpIX inside the cells (96,97). Moreover, in an in vitro model of myeloid leukemia, it has been shown that MYCN drives increased heme synthesis and that, in this system, the excess of PpIX produced is promptly exported out of the cells by ABCG2 to avoid cell toxicity (45).…”
Section: Heme Import/export/degradation and Cancermentioning
confidence: 99%
“…A number of PDT agents are known to be substrates of ABCG2. High ABCG2 expression decreases the intracellular accumulation and in vitro potency of the investigational PDT agents pheophorbide a [ 39 , 40 ], pyropheophorbide a methyl ester [ 41 ], and chlorin e6 [ 41 ]. There is also in vitro and in vivo evidence that ABCG2 can cause resistance to a PDT agent currently under clinical investigation, 2-(1-hexyloxethyl)-2-devinyl pyropheophorbide, commonly known as HPPH [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, ABCG2 is one of the DEGs from the shell gland of Youxian duck green eggshell line which is up-regulated expression in its gene family. ABCG2 is a member of the ABCG subfamily, also known as adenosine triphosphate binding cassette transporter G2, mainly located in the cell membrane, which regulates the expression of endogenous protoporphyrin [ 41 ]. Furthermore, we also found some DEGs from ABCB, ABCA, ABCC, ABCD subtribe, such as ABCB1 , it has been identified as potential unconjugated bilirubin transporters, which export the pigment from the cells [ 42 ].…”
Section: Discussionmentioning
confidence: 99%